Aleś Puszkin — czołowa postać białoruskiej awangardy? - Kuleszewicz, Anna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Avant-garde, a rebellious band of new trends and tendencies in art that appeared in the early 20th century, lasted for years being transformed, yielding the new forms of expression. It is also a trend of art most often associated with contemporaryBelarusian art (partially due to “school of Vitebsk”, Marc Chagall and Kazimir Malevich), still enjoying popularity in the country. One of the most recognizable Belarusian artistsis Ales Pushkin, born in 1965 in Bobr, associated with the Achremczuk’s National Schoolof Music and the Arts in Minsk and Vitebsk artistic environment. Pushkin is known for his indomitable, rebellious attitude towards the state regime. For many observers, art amateurs and even art critics, the character of his work immediately resembles avant-garde. However, as some researchers noted, Pushkins’ art enters a new dimension,paving the way towards new horizons of contemporary (avant-garde?) art of Belarus.